1990
DOI: 10.1017/s0003356100004906
|View full text |Cite
|
Sign up to set email alerts
|

Correlated responses to selection for cow fertility in a tropical beef herd

Abstract: Correlated responses to selection in a tropical beef herd for high (H) and low (L) estimated breeding value for pregnancy rate were measured over three calf crops. The H line calves were proportionately 0-04 lighter at weaning but during the ensuing dry season they lost less weight than L line animals, so that between the ages of 12 and 18 months there were no significant line differences in live weight. It was concluded that selection for cow fertility had not directly altered the progeny's growth rate. Tick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Age‐corrected scrotal circumference was consistently reported to be a useful method of assessing reproductive function in bulls (Table 1) because of the favourable relationship with a number of sperm traits (Brinks et al. 1978) and fertility (Mackinnon et al. 1990b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age‐corrected scrotal circumference was consistently reported to be a useful method of assessing reproductive function in bulls (Table 1) because of the favourable relationship with a number of sperm traits (Brinks et al. 1978) and fertility (Mackinnon et al. 1990b).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic markers of male reproductive traits with effects on female progeny. Age-corrected scrotal circumference was consistently reported to be a useful method of assessing reproductive function in bulls (Table 1) because of the favourable relationship with a number of sperm traits (Brinks et al 1978) and fertility (Mackinnon et al 1990b). Prepubertal basal serum follicle-stimulating hormone (FSH) concentration was identified as a potential candidate trait because of its role in the endocrine control of testicular function and its moderate correlation with Sertoli cell number (Moura and Erickson 1997) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in female reproductive characteristics by selection in the prepubertal ram for high LH response to GnRH challenge were demonstrated in sheep (Evans et al, 1989) and may exist in cattle as there is genetic variation (h 2 > 0.5) between young bulls in their ability to secrete testosterone in response to GnRH stimulation (Mackinnon et al, 1991). These genetically influenced hormonal control mechanisms coupled with reports that fertility is repeatable (Rudder et al, 1976;Goddard, 1980;Seifert et al, 1980;Entwistle, 1983Entwistle, , 1984Winter et al, 1985;Mackinnon, 1988;Mackinnon et al, 1987;O'Neill et al, 2000) suggest that an opportunity exists to genetically improve calf output in tropical genotypes in northern Australia, partly by reducing reproductive inefficiencies.…”
Section: Genetic Factors Associated With Reproductive Efficienciesmentioning
confidence: 99%
“…Mackinnon et al 1989;Prayaga 2004). The review of Davis (1993) identified significant within-breed genetic differences for female reproduction traits related to calf output, and results from a large divergent selection study for pregnancy rate in a tropical beef herd generated significant differences in pregnancy rate between the high and low lines Mackinnon et al 1990;Davis et al 1993). However, industry-wide improvement of female reproductive performance by genetic selection has generally proved difficult, mainly because of low heritabilities and the late expression of traits, and difficulties in capturing the necessary joining and reproductive data.…”
Section: Introductionmentioning
confidence: 99%
“…However, results are inconclusive. Several studies have shown improved pregnancy or calving rates to be associated with the age at puberty Morris et al 2000;Phocas and Sapa 2004) and Mackinnon et al (1990) postulated the selection response in female fertility in a divergently selected tropical beef herd was likely due to earlier sexual maturity. Mialon et al (2001) showed a positive genetic correlation between the age at the first oestrous and the postpartum to return to oestrus interval.…”
Section: Introductionmentioning
confidence: 99%